Differential Nutrient Uptake by Saltmarsh Plants Is Modified by Increasing Salinity - Carmona, Raquel; Muñoz, Rocío; Niell, F. Xavier (Frontiers in Plant Science, 2021)
In Southern European estuaries and associated salt marshes, the anthropogenic nutrient inputs, together with longer drought periods, are leading to increasing eutrophication and salinization of these coastal ecosystems. In this study, uptake kinetics of ammonium, nitrate and phosphate by three common plants in Palmones salt marsh (Southern Spain), Sarcocornia perennis ssp. alpini, Atriplex portulacoides and Arthrocnemum macrostachyum, were measured in hydroponic cultures. We also determined how these uptakes could be modified by increasing salinity, adding NaCl to the incubation medium (from 170 to 1025 mM). Kinetic parameters are analyzed to understand the competition of the three species for nutrient resources under realistic most frequent concentrations in the salt marsh. These results may also be useful to predict the possible changes in the community composition and distribution if trends in environmental changes persist. Atriplex portulacoides showed the highest Vmax for ammonium, the most abundant nutrient in the salt marsh, while the highest affinity for this nutrient was observed in A. macrostachyum. Maximum uptake rates for nitrate were much lower than for ammonium, without significant differences among species. The highest Vmax value for phosphate was observed in A. macrostachyum, whereas A. portulacoides presented the highest affinity for this nutrient. High salinity drastically affected the physiological response of these species, decreasing nutrient uptake. Sarcocornia perennis ssp. alpini and A. macrostachyum were not affected by salinity up to 510 mM NaCl, whereas A. portulacoides notably decreased its uptake capacity at 427 mM and even withered at 1025 mM NaCl. At current most frequent concentrations of ammonium and phosphate in the salt marsh, S. perennis ssp. alpini is the most favored species, from the nutritional point of view. However, A. portulacoides could enhance its presence if the increasing ammonium load continues, although a simultaneous salinization would negatively affect its nutritional physiology.